Formação de sujeitos leitores - Brandão, Marília Araújo Tittoni (2009)
This study presents a proposal for activities carried out with students attending the fifth grade of the Elementary Cycle at the Pedro Calmon State School, Salvador-BA, addressing the formation of citizens bearing increased critical reasoning, awareness and reading habits. The objective of this study was to highlight the importance of reading as a pedagogical act, taking into consideration the teacher/student interaction. In order to reach the objective proposed, the author analyzed variables impairing the formation of individuals fond of reading; the author also characterized attitudes, habits and feelings related to reading. A field survey was applied among students attending the fifth grade of the Elementary Cycle, in order to achieve a better understanding of those variables (attitudes and feelings). A questionnaire with 12 questions and in-class observations composed the tool used in the field survey. The methodology used for data collection was qualitative. The sample was composed of a whole fifth grade, i.e. 26 students. The study recognizes the difficulties faced by the low-income students to reading and the myth stating that the pleasure derived from reading does not supply the goods needed for survival, however it is extremely recommended to valuate the reading habits not just to meet the school curricula requirements, but rather to reflect about the role of every individual in the search for his/her own knowledge and in the formation of a critical awareness within the civil society.